Effects of N-acetylcysteine on aging cell and obesity complications in obese adults: a randomized, double-blind clinical trial - Sohouli, Mohammad Hassan; Eslamian, Ghazaleh; Malekpour Alamdari, Nasser; Abbasi, Maryam; Fazeli Taherian, Sepideh; Behtaj, Diba; Zand, Hamid (Frontiers in Nutrition, 2023)
We decided to conduct this study with the aim of investigating the effects of N-Acetylcysteine (NAC) on obesity complications and senescence of visceral adipose tissue in obese adults.The present study was conducted as a randomized clinical trial (RCT) (Clinical trial registry number: IRCT20220727055563N1) on 40 obese adults candidates for bariatric surgery, who were randomly assigned to receive 600 mg of NAC (n = 20) or placebo as a control (n = 20) for 4 weeks. During bariatric surgery, visceral adipose tissue was used to examine gene expression and senescence cells using SA-β-gal.Results: Our findings showed that intervention with NAC significantly reduces SA-β-gal activity (as a marker of senescence) and expression of p16 and interleukin 6 (IL-6) genes in the visceral adipose tissue compared to placebo in obese adults for 4 weeks. In addition, our findings showed the potential and beneficial effect of NAC administration on reducing the levels of inflammatory factors including IL-6 and high-sensitivity C-reactive protein (hs-CRP), as well as the level of fasting blood sugar (FBS), homeostatic model assessment of insulin resistance (HOMA-IR), and insulin compared to placebo after adjusting for confounders. No significant effect was indicated on anthropometric factors and lipid profile.Findings showed that NAC, in addition to having a potential beneficial effect on reducing some of the complications caused by obesity, seems to have synolytic/senomorphic potential as well.